Lightning injuries in sports: situations to avoid - Cherington, M. (Sports Medicine, 2001)
There is no absolute protection against lightning because of its random and capricious nature. However, the risk of being struck by lightning can be substantially reduced. There are general safety rules that apply to all athletic and recreational events. The athlete should have a proactive plan that can be instituted when storms approach. He/she should go to a safe shelter before the storm arrives and stay there until the danger is gone. Because the location, climate, terrain and playing site vary with different sporting activities, safety plans may have distinct elements for different recreational activities. Mountain climbers should know the weather patterns of their locale. The highest frequency of lightning strikes in the Rocky Mountains occurs between 11 am and 9 pm during the months of April to September. There is less chance of a hiker encountering lightning during the early morning hours. Many tourists are unaware of this pattern, which may possibly explain the finding that most lightning victims are visitors from other states. The bicyclist is as vulnerable as anyone in the open. In the event of lightning he/she should seek safe shelter and get off the bike. Rubber tires do not provide protection from lightning. Golfers continue to make the same mistakes year after year. Golfers should know to seek safe shelter (clubhouse or closed metal vehicle) before the storm arrives and not return prematurely to the golf course. They should avoid isolated trees, open fields, unsafe sheds and metal poles. They should separate from each other rather than gather together. Swimmers should get out of the pool and find a safe shelter. Safe areas do not include poolsides, under awnings or under trees. A nearby closed automobile may be the safest place until the danger is gone. Applying precautions when engaging in these sporting or recreational activities will help to minimise the risk of casualties or fatalities caused by lightning.